Do international investors enhance private firm value? Evidence from venture capital - Cumming, Douglas; Knill, April; Syvrud, Kelsey (Journal of International Business Studies, 2016)
We examine the impact of international venture capital investors on private firm success spanning 81 countries over the years 1995–2010. The data examined indicate that, relative to deals in which the investor base is purely domestic, private firms that have an international investor base have a higher probability of exiting via an initial public offering (IPO) and higher IPO proceeds. The evidence is consistent with the view that while the benefits of internationalization may be difficult and costly to manage, for those firms that succeed in managing cross-border coordination costs, there is potential value for an IPO firm. The benefits relative to the costs of internationalizing the investor base for private firms sold in acquisitions, by contrast, are much less pronounced. The most important source of this benefit appears to be access to capital.